Shaping history 100 great leaders - Mooney, Brian (London Arcturus, 2004)
Throughout history, certain individuals have risen to the top. Driving others on, leading by example and leading from the front, they have shaped history. 100 Great Leaders looks in depth at some of the most renowned leaders, the most notorious leaders and the most unlikely leaders.
"From antiquity to the present"--Cover.
Keywords: Biography